Comparative CRISPR type III-based knockdown of essential genes in hyperthermophilic Sulfolobales and the evasion of lethal gene silencing. Issue 3 (4th March 2021) - Zink, Isabelle Anna; Fouqueau, Thomas; Tarrason Risa, Gabriel; Werner, Finn; Baum, Buzz; Bläsi, Udo; Schleper, Christa
ABSTRACT: CRISPR type III systems, which are abundantly found in archaea, recognize and degrade RNA in their specific response to invading nucleic acids. Therefore, these systems can be harnessed for gene knockdown technologies even in hyperthermophilic archaea to study essential genes. We show here the broader usability of this posttranscriptional silencing technology by expanding the application to further essential genes and systematically analysing and comparing silencing thresholds and escape mutants. Synthetic guide RNAs expressed from miniCRISPR cassettes were used to silence genes involved in cell division ( cdvA ), transcription ( rpo8 ), and RNA metabolism ( smAP2 ) of the two crenarchaeal model organisms Saccharolobus solfataricus and Sulfolobus acidocaldarius . Results were systematically analysed together with those obtained from earlier experiments of cell wall biogenesis ( slaB ) and translation ( aif5A ). Comparison of over 100 individual transformants revealed gene-specific silencing maxima ranging between 40 and 75%, which induced specific knockdown phenotypes leading to growth retardation. Exceedance of this threshold by strong miniCRISPR constructs was not tolerated and led to specific mutation of the silencing miniCRISPR array and phenotypical reversion of cultures. In two thirds of sequenced reverted cultures, the targeting spacers were found to be precisely excised from the miniCRISPR array, indicating a still hypothetical, but highly active recombination system acting on the dynamics of CRISPR spacer arrays. Our results indicate that CRISPR type III – based silencing is a broadly applicable tool to study in vivo functions of essential genes in Sulfolobales which underlies a specific mechanism to avoid malignant silencing overdose.